ChemInform Abstract: Theoretical Insight into the Selectivities of Copper‐Catalyzing Heterogeneous Reduction of Carbon Dioxide. Issue 6 (21st January 2016) - Sun, Xitong; Cao, Xiaoming; Hu, P.
Abstract: Review: 74 refs.